2009
DOI: 10.1111/j.1742-4658.2009.06880.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and mechanistic characterization of Mycobacterium tuberculosis glutamyl–tRNA synthetase and determination of its oligomeric structure in solution

Abstract: Mycobacterium tuberculosis glutamyl-tRNA synthetase (Mt-GluRS), encoded by Rv2992c, was overproduced in Escherichia coli cells, and purified to homogeneity. It was found to be similar to the other well-characterized GluRS, especially the E. coli enzyme, with respect to the requirement for bound tRNA Glu to produce the glutamyl-AMP intermediate, and the steady-state kinetic parameters k cat (130 min ) and K M for tRNA (0.7 lm) and ATP (78 lm), but to differ by a one order of magnitude higher K M value for l-Glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…An interaction between GluRS and GluTR has been proposed [29,30]. Our data indicate that a complex between GluRS and GluTR from A. ferrooxidans is also formed (O. Orellana, D. Pezoa, P. Alamos, unpublished results), which could potentially channel Glu-tRNA directly for tetrapyrrole synthesis.…”
Section: Discussionsupporting
confidence: 64%
“…An interaction between GluRS and GluTR has been proposed [29,30]. Our data indicate that a complex between GluRS and GluTR from A. ferrooxidans is also formed (O. Orellana, D. Pezoa, P. Alamos, unpublished results), which could potentially channel Glu-tRNA directly for tetrapyrrole synthesis.…”
Section: Discussionsupporting
confidence: 64%
“…In humans upon phosphorylation, GluProRS is released from the MSC and associates with NS1-associated protein 1, ribosomal protein L13a, and glyceraldehyde-3-phosphate dehydrogenase to silence translation of certain mRNAs related to the inflammatory response (30). In Chlamydomonas reinhardtii and Mycobacterium tuberculosis glutamyl-tRNA reductase (GluTR) binds GluRS likely to divert Glu-tRNA Glu synthesis from use in translation to tetrapyrrole biosynthesis (31,32). Given that many archaea posses GluTR (33), there may be competition for binding with ND-GluRS between GatDE and GluTR.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that heme content in GluTR varied according to the concentration of heme provided in the culture medium, and that heme bound preferentially to the dimeric state of the protein. 92 Variability in heme content for GluTR was reported for two other species, namely C. vibrioforme (1 heme per monomer) 93 and M. tuberculosis (1 heme per 16 monomers) 94 GluTR. Binding of heme was accompanied by the formation of a low-spin complex with a Soret peak maximum appearing at 420 nm.…”
Section: Glutamyl-trna Reductasementioning
confidence: 95%